Organellar genomes of giant kelp from the southern hemisphere. Issue 1 (31st December 2023) - Iha, Cintia; Layton, Cayne; Flentje, Warren; Lenton, Andrew; Johnson, Craig; Fraser, Ceridwen I.; Willis, Anusuya
ABSTRACT: Macrocystis pyrifera is a foundation species that creates kelp forests and supports essential ecosystem services across coastal environments. Over the past half-century, more than 95% of giant kelp forests have declined around Tasmania and Australia due to climate change, causing a near-complete loss of the ecosystems and services they support. Compared with northern hemisphere giant kelp ecosystems, Australian populations have received little research attention in genomic and other genetic analyses. We present the complete mitochondrial and chloroplast genomes of Macrocystis pyrifera from Tasmania. Both organellar genomes were similar to published Laminariales genomes in length, GC content, gene composition and synteny. A phylogeny constructed by combining protein-coding genes from both genomes showed Tasmanian specimens clustered with M. pyrifera specimens from the northern hemisphere. Genetic differences in protein genes between the Tasmanian M. pyrifera and the northern hemisphere specimens were overall low, but some ribosomal protein genes presented higher values of nonsynonymous mutations. The most divergent gene, the mitochondrial conserved hypothetical protein ORF377, can provide insights into the evolution of the species. This gene has been proposed as a suitable molecular marker for population genetic research in Fucales and may also be helpful for intraspecific studies of M. pyrifera . The complete mitochondrial and chloroplast genomes of Tasmanian M. pyrifera provide important genetic data and critical information for further evolutionary and population studies and for managing these endangered and disappearing populations.